(untitled) (Journal of the College of Basic Education, 2022)
condensation of EDTA and 2,4-Diamino-6-Phenyl 1,3,5 triazine as a chelating polymer which was complexed with metal ions such as Ti,Co,Cr,Ni,Fe ions. These prepared complexes were characterized by elemental analysis and infrared and Ultraviolet spectroscopies. The physical properties were measured. Intrinsic viscosities were calculated by using Ostwald viscometer.